Strategi Pemasaran Digital Melalui Instagram pada UMKM Telur Asin "Ulfa" - Zahrotussolikhah, Afla; Muhammad Akbar Baihaqi; Novi Vahim Varhana; Syifaul Azza Amin (Fusion: Jurnal Pengabdian kepada Masyarakat, 2025)
UMKM play a vital role in regional economic growth, but many business actors still experience limitations in the use of technology, especially in terms of digital marketing. The “Ulfa” Salted Eggs UMKM in Gedangan Village, Tulungagung Regency, faces obstacles in a marketing system that is still traditional and a lack of understanding of digital marketing. The owner's limitations in using technology are the main obstacles in implementing digital marketing strategies. This community service activity aims to increase the effectiveness of the marketing of these UMKM through a digital marketing approach using Instagram social media. The method of implementing the activity includes interviews, observations, documentation, and Focus Group Discussions (FGD) with business owners. The results of this activity include creating a logo as part of strengthening brand identity, as well as training in creating and managing Instagram accounts as a medium for product promotion. The implementation of this digital marketing is expected to expand market reach, increase competitiveness, and encourage the sustainability of the “Ulfa” Salted Eggs business in facing marketing obstacles in the increasingly competitive digital era.